A New Protocol for Anticoagulation With Tirofiban During Flow Diversion. Issue 5 (May 2016) - Chalouhi, Nohra; Jabbour, Pascal; Daou, Badih; Starke, Robert M.; Shields, Bridget; Hasan, David M.
Abstract : BACKGROUND: Flow diversion is increasingly used to treat intracranial aneurysms. In previous reports, patients were pretreated with aspirin and clopidogrel before the intervention for the prevention of thromboembolic complications. OBJECTIVE: To assess the safety and efficacy of a new protocol for anticoagulation using tirofiban during flow diversion. METHODS: All patients received a 0.10–μg·kg −1 ·min −1 maintenance infusion of tirofiban intraoperatively without a loading dose. All patients were loaded with aspirin (325 mg) and clopidogrel (600 mg) just before the procedure or intraoperatively. No patient was pretreated with aspirin or clopidogrel. Thromboembolic and hemorrhagic complications were recorded. RESULTS: A total of 46 patients were treated with this protocol. Six patients (13%) had sustained a subarachnoid hemorrhage and were treated with the Pipeline Embolization Device within 24 hours of aneurysm rupture. The mean number of devices was 1.2 ± 0.66; adjunctive coiling was performed in 3 patients (6.5%). There were 2 complications (4.3%), 1 thromboembolic (2.2%) and 1 hemorrhagic (2.2%; monocular vision loss from occlusion of the central retinal artery in 1 patient and a parenchymal hemorrhage managed conservatively in another patient). No patient developed thrombocytopenia or retroperitoneal, gastrointestinal, or genitourinary bleeding. Of 46 patients, 44 (95.7%) had a modified Rankin Scale score of 0 to 2 at their follow-up visit. CONCLUSION: A protocol of anticoagulation with tirofiban during flow diversion has an excellent safety profile. This protocol provides a reasonable alternative to pretreatment with aspirin and clopidogrel and is useful in patients with ruptured aneurysms or when the use of a stent is unexpected. ABBREVIATIONS: Gp IIb/IIIa, glycoprotein IIb/IIIa PED, Pipeline Embolization Device PRU, P2Y12 reaction units